1987
DOI: 10.1002/hlca.19870700818
|View full text |Cite
|
Sign up to set email alerts
|

17O‐NMR Spectra of Cyclopropenones and Tropone. Oxygen Exchange with Water

Abstract: ~~~ ~Whereas tropone (2) and a cyclopropanone 5 show rather normal ketone signals in their "0-NMR spectra, the two cyclopropenones la, and l b exhibit exceptionally high shielding, indicating a structure closer to a -0-formula than to a ketone. For comparison, an enolate and several phenolates have been measured. In order to test the ketonic character, the nucleophilic addition of water was determined by the rate of isotopic 0-exchange between ketone and water; 2 exchanged ca. 20 times slower than acetophenone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…On the other hand, polarization of the carbonyl group, expressed as n-bond order [32] [8], is considered to influence also the C-0 bond length. We have found that (high) shielding and (high) bond length go parallel in the cyclopropenones [9]. In the sydnonetype compounds, however, high shielding of the exocyclic 0-atom goes with normal C=O bond length (and normal IR vibrations); at the same time, the ring 0-atom of these compounds shows normal furan-type shielding, but a weakened bond to its neighbour.…”
Section: Ementioning
confidence: 91%
See 2 more Smart Citations
“…On the other hand, polarization of the carbonyl group, expressed as n-bond order [32] [8], is considered to influence also the C-0 bond length. We have found that (high) shielding and (high) bond length go parallel in the cyclopropenones [9]. In the sydnonetype compounds, however, high shielding of the exocyclic 0-atom goes with normal C=O bond length (and normal IR vibrations); at the same time, the ring 0-atom of these compounds shows normal furan-type shielding, but a weakened bond to its neighbour.…”
Section: Ementioning
confidence: 91%
“…360 ppm [7]; cyclisation exerts only a moderate influence [7] [31]; we found, e.g., 6, (benzene, 85"; in parenthesis: linewidth in Hz) for benzyl benzoate at 343 (300; =0) and 157 (160; -0-), and for phthalide (11) at 325 (90; =0) and 168 (50; -0-). On the other hand, completely polarized formulae like 1B-D present an enolate-type structure for the exocyclic 0-atom; we have shown that the enolate PhC(0-)=CHMe resonates at 137, phenolate PhO-at 158, andp-nitrophenolate at 210 ppm [9]. Even though it is difficult to account for the influence of the ring 0-atom on the exocyclic enolate 0, the 6, values found for the mesoionic compounds fit better a highly shielded exocyclic 0-atom, as symbolized by formula 1B.…”
Section: Ementioning
confidence: 95%
See 1 more Smart Citation
“…The interest in compounds of the cyclopropenone series stems from the inherent polar pseudoaromatic structures representing two mesomeric forms (1) $ (2) [1,2] (Scheme 1), high strain energies, planarity, chemical reactivity of the cyclopropene moiety [1][2][3], and possible practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The low kinetic stability 2,3 of the unsubstituted parent compound can usually be increased by substitution with electron-donating or bulky groups. Hitherto, cyclopropenones with alkoxy, 4 dialkylamino, 5,6 alkylthio, [7][8][9] alkylseleno, 10 and alkyltelluro 10 (2) groups have been reported.…”
Section: Introductionmentioning
confidence: 99%